Evaluación de la disminución en la carga energética mediante el re-diseño del equipo de Bombeo Mecánico utilizando una Bomba CBM para un pozo petrolero (2018)
Currently, the Mechanical Pumping Artificial Lift System is one of the most used production methods in some fields in Colombia, in particular, the study oil well located in the Middle Magdalena Valley Basin, presents several problems that generate a amount of power in the engine. In this project, a decrease in the energy load generated by the pumps in the Artificial Pumping Mechanic System is sought through the use of the CBM Pump in a particular oil well. To achieve this, the design proposed for the company is taken into account, support for the design of the system taking into account the API 11-L method. Subsequently, the design of the Mechanical Pumping equipment is evaluated using the CBM pump by comparison with a conventional design simulated in Rodstar, in this way the energy consumption generated by a conventional pump and generated by a CBM Pump can be determined. Finally, the evaluation of the financial viability of the project is carried out through the methodology of the Net Present Value and the Uniform Annual Cost Equivalent that allows the analysis of the reduction of the investment and operation costs associated to the energy consumption in the oil well.